Soda Taxes: The Importance of Analysing Policy Processes; Comment on "The Untapped Power of Soda Taxes: Incentivising Consumers, Generating Revenue, and Altering Corporate Behaviours" - Yann Le Bodo; Philippe De Wals (Kerman University of Medical Sciences, 2018)
Sarah A. Roache and Lawrence O. Gostin's recent editorial comprehensively presents soda taxation rationales from a public health perspective. While we essentially agree that soda taxes are gaining momentum, this commentary expands upon the need for a better understanding of the policy processes underlying their development and implementation. Indeed, the umbrella concept of soda taxation actually covers a diversity of objectives and mechanisms, which may not only condition the feasibility and acceptability of a proposal, but also alter its impact. We briefly highlight some conditions that may have influenced soda tax policy processes and why further theory-driven case studies may be instructive.